2016
DOI: 10.3892/etm.2016.3992
|View full text |Cite|
|
Sign up to set email alerts
|

Anthelmintic drug albendazole arrests human gastric cancer cells at the mitotic phase and induces apoptosis

Abstract: As microtubules have a vital function in the cell cycle, oncologists have developed microtubule inhibitors capable of preventing uncontrolled cell division, as in the case of cancer. The anthelmintic drug albendazole (ABZ) has been demonstrated to inhibit hepatocellular, ovarian and prostate cancer cells via microtubule targeting. However, its activity against human gastric cancer (GC) cells has remained to be determined. In the present study, ABZ was used to treat GC cells (MKN-45, SGC-7901 and MKN-28). A a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…Despite the several treatment modalities for cutaneous SCC, there is still a demand for novel pharmacotherapy that is more efficacious and safe. The repurposing/repositioning of drugs that have already been approved for other diseases is considered as an alternative way to develop new drugs, because time-consuming and expensive process can be avoided or shortened [21, 22]. In this study, we demonstrated that an antiparasitic drug albendazole has the potential to induce apoptosis of cutaneous SCC cells via triggering ER stress and reduces the stemness of SCC cells via regulation of β -catenin signaling.…”
Section: Discussionmentioning
confidence: 78%
“…Despite the several treatment modalities for cutaneous SCC, there is still a demand for novel pharmacotherapy that is more efficacious and safe. The repurposing/repositioning of drugs that have already been approved for other diseases is considered as an alternative way to develop new drugs, because time-consuming and expensive process can be avoided or shortened [21, 22]. In this study, we demonstrated that an antiparasitic drug albendazole has the potential to induce apoptosis of cutaneous SCC cells via triggering ER stress and reduces the stemness of SCC cells via regulation of β -catenin signaling.…”
Section: Discussionmentioning
confidence: 78%
“…Any drug that can activate through various mechanisms the apoptotic pathway or inhibit the endogenous anti-apoptotic molecules is a strong candidate to become an efficient anticancer agent. As reported by a great number of studies, ABZ can induce apoptosis through various mechanisms; in human gastric cancer cells, the ABZ anticancer activity emerged due to its ability to interfere with microtubule formation and function, causing mitotic arrest and subsequently inducing apoptosis [78]. The same microtubule disrupting ability was employed as anticancer treatment by Patel et al in small cell lung cancer and metastatic melanoma cell lines [8].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Table 1 ( 4 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ) summarizes the antitumorigenicity of benzimidazole anthelmintics on cancer cell lines. Benzimidazole anthelmintics inhibit the progression of cancer through a variety of mechanisms.…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%